Advantages of Arthroscopic Transosseous Suture Repair of the Rotator Cuff without the Use of Anchors - Kuroda, Shigehito (Springer US, 2013)
BACKGROUND: Although arthroscopic anchor suturing is commonly used for rotator cuff repair and achieves good results, certain shortcomings remain, including difficulty with reoperation in cases of retear, anchor dislodgement, knot impingement, and financial cost. In 2005, we developed an anchorless technique for arthroscopic transosseous suture rotator cuff repair. DESCRIPTION OF TECHNIQUE: After acromioplasty and adequate footprint decortication, three K-wires with perforated tips are inserted through the inferior margin of the greater tuberosity into the medial edge of the footprint using a customized aiming guide. After pulling the rotator cuff stump laterally with a grasper, three K-wires are threaded through the rotator cuff and skin. Thereafter, five Number 2 polyester sutures are passed through three bone tunnels using the perforated tips of the K-wires. The surgery is completed by inserting two pairs of mattress sutures and three bridging sutures. METHODS: We investigated the retear rate (based on MR images at least 1 year after the procedure), total score on the UCLA Shoulder Rating Scale, axillary nerve preservation, and issues concerning bone tunnels with this technique in 384 shoulders in 380 patients (174 women [175 shoulders] and 206 men [209 shoulders]). Minimum followup was 2 years (mean, 3.3 years; range, 2–7 years). Complete followup was achieved by 380 patients (384 of 475 [81%] of the procedures performed during the period in question). The remaining 91 patients (91 shoulders) do not have 1-year postsurgical MR images, 2-year UCLA evaluation or intraoperative tear measurement, or they have previous fracture, retear of the rotator cuff, preoperative cervical radiculopathy or axillary nerve palsy, or were lost to followup. RESULTS: Retears occurred in 24 patients (24 shoulders) (6%). The mean overall UCLA score improved from a preoperative mean of 19.1 to a score of 32.7 at last followup (maximum possible score 35, higher scores being better). Postoperative EMG and clinical examination showed no axillary nerve palsies. Bone tunnel-related issues were encountered in only one shoulder. CONCLUSIONS: Our technique has the following advantages: (1) reoperation is easy in patients with retears; (2) surgical materials used are inexpensive polyester sutures; and (3) no knots are tied onto the rotator cuff. This low-cost method achieves a low retear rate and few bone tunnel problems, the mean postoperative UCLA score being comparable to that obtained by using an arthroscopic anchor suture technique. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Instructions for Authors for a complete description of levels of evidence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-013-3148-7) contains supplementary material, which is available to authorized users.